Students’ Perception on the Online Learning through Google Meet and YouTube Channel during Pandemic Situation - Solihah, Yuni Awalaturrohmah (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
This study investigated the students’ perception of their online learning during pandemic situations, especially in the Structure and Written Expression Section of TOEFL Preparation Class. The students obtained the material of the Structure and Written Expression Section of TOEFL through video-conferences by Google Meet as well as learning videos by YouTube Channel. This focused on the students’ perception between Google Meet and YouTube Channel in the online learning of TOEFL Preparation Class in the fourth Semester Students of UCIC Cirebon. This was a qualitative study that obtained the data from the questionnaire and interview. The findings showed that the students were able to comprehend, be active to ask, and to interact with the lecturer during online learning through Google Meet as a video conference learning. Moreover, online learning through YouTube Channel made it easy to comprehend replaying the videos, but there was no interaction between students and lecturer. This study suggests the English lecturers discover the best media of online learning in order to enhance the students’ competences, especially in TOEFL Preparation Class.